2012
DOI: 10.1080/00223131.2012.676820
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio study of hydrogen diffusion in zirconium oxide

Abstract: Hydrogen diffusion in monoclinic and tetragonal zirconium oxides has been studied by electronic state calculations. In both structures, the optimized hydrogen site lies near the center of a distorted fluorite structure. The activation energy was calculated to be 120-200 kJ/mol, which is similar to experimentally measured values. The effects of compressive stress, alloying elements, and oxygen defects are considered individually. Compressive stress reduces the hydrogen diffusion coefficient by 40%/GPa. Oxygen d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…All the deuterium concentrations are normalised by the concentration at the outer surface, Cs. Fitting to this equation yields diffusion coefficients of about 10 -20 m 2 /s at 360 °C, very close to previous experimental results that lie between 10 -18 and 10 -21 m 2 /s [38][39][40][41]. Our results show that the pre-transition sample Z4-5 (61 days corrosion time) has a higher deuterium diffusion coefficient of 9.1 ± 0.2 × 10 −20 m 2 /s than that in sample Z4-9 (106 days corrosion time) of 5.4 ± 0.2 × 10 −20 m 2 /s.…”
Section: Sputtering Ratesupporting
confidence: 87%
“…All the deuterium concentrations are normalised by the concentration at the outer surface, Cs. Fitting to this equation yields diffusion coefficients of about 10 -20 m 2 /s at 360 °C, very close to previous experimental results that lie between 10 -18 and 10 -21 m 2 /s [38][39][40][41]. Our results show that the pre-transition sample Z4-5 (61 days corrosion time) has a higher deuterium diffusion coefficient of 9.1 ± 0.2 × 10 −20 m 2 /s than that in sample Z4-9 (106 days corrosion time) of 5.4 ± 0.2 × 10 −20 m 2 /s.…”
Section: Sputtering Ratesupporting
confidence: 87%
“…As reported, oxides are notorious for fast diffusion of hydrogen [18]. Although metal gate was deposited on ZrO2 above the channel, hydrogen ions (H + ) can first diffuse vertically in the ZrO2 layer in the gap between gate and source (drain), which was not covered by Ni, then diffuse laterally under the Au/Ni gate through ZrO2 rendering reactivation of H + with In2O3 at the ZrO2/InAs interface.…”
Section: Xps Measurementmentioning
confidence: 99%
“…Raman spectroscopy measurement revealed that the stress varies cyclically and can be as large as several GPa 7 . DFT calculations found that under 1GPa compressive stress hydrogen diffusion coefficient in tetragonal ZrO 2 is only about 60% of the coefficient without stress at 600 K 15 . It is worth noting that there is also literature arguing that the diffusion of hydrogen through the barrier oxide layer is not the rate-limiting step 21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…Besides the oxide morphology, additive elements (e.g., Fe, Cr, Nb, Sn and Ni) in different Zr alloys have substantial effects on the H pickup fraction. These elements may either behave like trapping sites and directly decrease the hydrogen diffusivity in the oxide 14,15 , or they may form second phase precipitates that have been hypothesized to be a preferred path for hydrogen migration or a source for pores or cracks formation [16][17][18] . Due to the lattice mismatch between Zr oxide and metal, high compressive stress is generated in the oxide near the interface 19,20 .…”
Section: Introductionmentioning
confidence: 99%